The impact of SLE on health-related quality of life assessed with SF-36: a systemic review and meta-analysis. (March 2019) - Gu, M; Cheng, Q; Wang, X; Yuan, F; Sam, NB; Pan, H; Li, B; Ye, D
Objective: To evaluate the impact of systemic lupus erythematosus (SLE) on health-related quality of life (HRQoL) assessed with SF-36 and explore factors associated with HRQoL in SLE patients. Methods: A random-effect meta-analysis was performed to calculate extracted data. Sensitivity and subgroup analyses were performed to distinguish sources of heterogeneity. Results: A total of 36 articles were finally included in this meta-analysis, including 6510 patients. The pooled mean scores of SF-36 physical component summary and mental component summary were 46.10 (95% confidence interval (CI): 43.09–49.10) and 50.37 (95% CI: 47.78–52.87), respectively. Spearman's correlation analysis found that mean age, proportion of female participants, and publication decades were negatively associated with some of the SF-36 domains. Sample size and SLEDAI were positively associated with some of the SF-36 domains. Patients with SLE have lower HRQoL in comparison to the general population. Conclusions: SLE has a significant impact on HRQoL, which proves that the necessity of improving HRQoL in SLE patients cannot be ignored. Measuring HRQoL should be considered as an indispensable part of the overall evaluation of health conditions of SLE patients.